Violences à l’acte, violences dans l’acte : pour une histoire des théâtres féministes états-uniens - Madeleine Planeix-Crocker (Les Cahiers de l'École du Louvre)
A look back at the origins of American feminist theatres, built in parallel with the civil rights movements as from the 1960s, allows the history of these theatres to be rehabilitated. Theatre practice developed into a vehicle for political demands, and the stage into a space for representing the social and physical/moral violence suffered by identified women in artistic circles and further afield. From the first feminist theatre companies to the emergence of individual practices, the theatre – from the writing of a play to its staging – also provides a channel for alternative, utopian imaginative worlds free from violence and oppression. Developed through the prism of feminist, queer and intersectional critical theories, this work reveals the issues that were at stake at that artistic moment and discusses its contemporary heritage.